Potensi Cangkang Telur Ayam dan Cangkang Telur Bebek sebagai Bioadsorben Logam Pb dari Limbah Cair Industri Farmasi: Potency of Chicken Eggshells and Duck Eggshells as Pb Metal Bioadsorbents from Pharmaceutical Industry Liquid Waste - Lisna Dewi; Ginayanti Hadiesobroto; Hesty Nuur Hanifah (KOVALEN: Jurnal Riset Kimia, 2022)
The pharmaceutical industry liquid waste is one of the wastes that have the potential to produce waste containing heavy metals. One of the highest metal contaminants originating from the pharmaceutical industry is lead (Pb). Pb metal can cause health problems and pollute the environment. One way to treat Pb waste is by the adsorption process using bioadsorbent. The eggshell waste can be used as an adsorbent to absorb heavy metals. The eggshell contains calcium carbonate, therefore it can be used as an adsorbent. This study aims to determine the optimum pH, optimum mixing time, and optimum mass of chicken eggshell powder and duck eggshell powder, and to determine the comparison of the effectiveness of adsorption between chicken eggshell powder and duck eggshell powder as bioadsorbent of heavy metal Pb in pharmaceutical industry wastewater by using Atomic Absorption Spectrophotometer (AAS) at a wavelength of 283.3 nm. The results showed that the eggshell samples had the optimum pH at pH 4, the optimum mixing time was 45 minutes, and the optimum mass was 125 mg, with the effectiveness of Pb adsorption of 92.75%. While the duck eggshell samples obtained the optimum pH at pH 2, the optimum mixing time was 30 minutes, and the optimum mass was 125 mg, with the effectiveness of Pb adsorption of 93.66%. Chicken and duck eggshells have the potential to be used as an alternative bioadsorbent in wastewater treatment.